2004
DOI: 10.1136/bjo.2003.019232
|View full text |Cite
|
Sign up to set email alerts
|

The direct brow lift: efficacy, complications, and patient satisfaction

Abstract: Background/aims: The direct brow lift operation can be used to treat brow ptosis arising from either involutional changes or facial nerve palsy. The authors reviewed their experience with this operation to establish its efficacy and complication rate in the light of concerns over poor scar cosmesis and forehead paraesthesiae in the postoperative period. Methods: A retrospective review of patients undergoing direct brow lifting from 1989 to 2002 was conducted, and information gained on patient satisfaction by q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
109
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(109 citation statements)
references
References 16 publications
0
109
0
Order By: Relevance
“…Endoscopic methods of brow lifting have comparable success rates to open coronal lifting, but a significantly lower incidence of complications and a faster rehabilitation time [26]. Withey et al [27] reported the complications of endoscopic techniques as postoperative numbness, itching, hair loss, tissue swelling and asymmetry.…”
Section: Endoscopic Techniquesmentioning
confidence: 97%
See 2 more Smart Citations
“…Endoscopic methods of brow lifting have comparable success rates to open coronal lifting, but a significantly lower incidence of complications and a faster rehabilitation time [26]. Withey et al [27] reported the complications of endoscopic techniques as postoperative numbness, itching, hair loss, tissue swelling and asymmetry.…”
Section: Endoscopic Techniquesmentioning
confidence: 97%
“…This technique is not appropriate for those patients with a high hairline or those with thinning hair. There are numerous potential complications following this procedure including sensory and motor nerve dysfunction, skin necrosis, permanent overcorrection, alopecia, abnormal soft tissue contour, and eyebrow and eyelid asymmetry [26].…”
Section: Coronal Brow Liftmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were asked to rate the success of their operations across four dimensions using a novel grading scale similar to others used in the literature to assess postoperative facial cosmesis 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have also found surgical skin scars at other sites to be less prominent in elderly patients, when compared with younger patients. 37,38 There are some limitations for the present study. The need for revision was highest in patients not undergoing silicone stent placement.…”
Section: Eyementioning
confidence: 99%